2017
DOI: 10.3389/fpls.2017.00297
|View full text |Cite
|
Sign up to set email alerts
|

VaERD15, a Transcription Factor Gene Associated with Cold-Tolerance in Chinese Wild Vitis amurensis

Abstract: Early responsive to dehydration (ERD) genes can be rapidly induced to counteract abiotic stresses, such as drought, low temperatures or high salinities. Here, we report on an ERD gene (VaERD15) related to cold tolerance from Chinese wild Vitis amurensis accession ‘Heilongjiang seedling’. The full-length VaERD15 cDNA is 685 bp, including a 66 bp 5′-untranslated region (UTR), a 196 bp 3′-UTR region and a 423 bp open reading frame encoding 140 amino acids. The VaERD15 protein shares a high amino acid sequence sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 68 publications
(85 reference statements)
0
33
0
Order By: Relevance
“…The ERD (Early Responsive to Dehydration) genes can be rapidly induced upon abiotic stresses such as drought, low temperature, or salinity [62]. Belonging to a highly conserved family, ERD15 is not only a central component of several stress responses in Arabidopsis but also involved in stomatal closure.…”
Section: Sto Had Crosstalk With Aba Upon Uv-b Radiationmentioning
confidence: 99%
“…The ERD (Early Responsive to Dehydration) genes can be rapidly induced upon abiotic stresses such as drought, low temperature, or salinity [62]. Belonging to a highly conserved family, ERD15 is not only a central component of several stress responses in Arabidopsis but also involved in stomatal closure.…”
Section: Sto Had Crosstalk With Aba Upon Uv-b Radiationmentioning
confidence: 99%
“…Vitis vinifera L. is sensitive to low temperature. The major species of grapes cultivated in China is the European grape, which has poor cold resistance ( Yu et al, 2017 ). Consequently, freezing temperatures in winter and cold snaps during spring exert strong negative impacts on the grape production.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this may be an increase of their chloroplast content, pointing to VyRCHC114's possible involvement in the regulation of chlorophyll biosynthesis pathway as an E3 ubiquitin ligase. Nonetheless, we also examined the expression of genes known to play a major role in drought stress responses of plants [50][51][52]. Our results revealed that the expression levels of these genes were signi cantly higher in VyRCHC114-overexpressed than EV-transformed Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 91%